2019
DOI: 10.1007/s00209-019-02450-2
|View full text |Cite
|
Sign up to set email alerts
|

Partial silting objects and smashing subcategories

Abstract: We study smashing subcategories of a triangulated category with coproducts via silting theory. Our main result states that for derived categories of dg modules over a non-positive differential graded ring, every compactly generated localising subcategory is generated by a partial silting object. In particular, every such smashing subcategory admits a silting t-structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The case of a large presilting object will be discussed in a forthcoming paper by Angeleri Hügel, Pauksztello and Vitória. The paper will be devoted to partial silting objects. It will be shown that in the derived category D(A) of an arbitrary ring A every set Σsans-serifKbfalse( proj (A)false) of compact objects admits a partial silting object T such that normalΣZ=TZ, in analogy with a result for two‐term complexes from .…”
Section: Classification Resultsmentioning
confidence: 99%
“…The case of a large presilting object will be discussed in a forthcoming paper by Angeleri Hügel, Pauksztello and Vitória. The paper will be devoted to partial silting objects. It will be shown that in the derived category D(A) of an arbitrary ring A every set Σsans-serifKbfalse( proj (A)false) of compact objects admits a partial silting object T such that normalΣZ=TZ, in analogy with a result for two‐term complexes from .…”
Section: Classification Resultsmentioning
confidence: 99%